Faktor-Faktor Yang Berhubungan Dengan Perilaku Skrining TB Pada Kontak Serumah di Kabupaten Pandeglang - Nono Sukarna; Mamat Lukman; Sheizi Prista Sari (STIKes Karsa Husada Garut, 2015)
Indonesia represent countris burden high as contributor of case of tuberculosis to four after India, Chinese and African South. Tuberculosis represent contagion with number mortality one among other contagion. Disease of tuberculosis because of catching tuberculosis mycobacterium pass air. Date of Public Health Service in Pandeglang District show house contact with patient of tuberculosis doing screening only 5%, though ought to all house contact do skrining before medication started by patient of tuberculosis. Low of him of screening tuberculosis at house contact result infection continue happened, found overdue case and many symptom by patient of medication after even death. This research aim to know factors related to behavior of tuberculosis screening at house contact. This Research type is quantitative research with analytic desain of corelasional with approach of study control case. Its research sample that is family contact house with patient of tuberculosis in District of Pandeglang counted 250 family. Technique intake of sampel by purposive sampling. Pursuant to result of research that there is relation of signifikan between age, gender, nuptials status, race, education, work, distance, transportation, time, health insurance, and knowledge with behavior of tuberculosis screening and no relation of signifikan between earnings, expense of, relation with patient of tuberculosis, family type, belief health and perceived of need with behavior of tuberculosis screening. Variable most dominant its relation with behavior of tuberculosis screening at house contact in Pandeglang District year 2015 that is work variable.